Antarctic Krill Oil Exhibited Synergistic Effects with Nobiletin and Theanine on Regulating Ligand‐Specific Receptor‐Mediated Transcytosis in Blood–Brain Barrier by Inhibiting Alkaline Phosphatase in SAMP8 Mice. Issue 8 (8th March 2023) - Wang, Cheng‐Cheng; Kong, Jing‐Ya; Xue, Chang‐Hu; Zhang, Tian‐Tian; Wang, Yu‐Ming
Abstract: Blood−brain barrier (BBB) impairment is related to the development of Alzheimer's disease (AD), which is dependent not only on tight junction but also on transcytosis of brain endothelial cells (BECs) in the BBB. Aging induces the decrease of ligand‐specific receptor‐mediated transcytosis (RMT) and the increase of non‐specific caveolar transcytosis in BECs, which lead to the entry into parenchyma of neurotoxic proteins and the smaller therapeutic index in central nervous system drug delivery, further provoking neurodegenerative disease. A previous study suggests that sea‐derived Antarctic krill oil (AKO) exhibits synergistic effects with land‐derived nobiletin (NOB) and theanine (THE) on ameliorating memory and cognitive deficiency in SAMP8 mice. However, it is still unclear whether BBB change is involved. Hence, the effects of AKO combined with NOB and THE on aging‐induced BBB impairment, including tight junction between BECs, ligand‐specific RMT, and non‐specific caveolar transcytosis in BECs, are investigated. The results suggest that AKO exhibits synergistic effects with NOB and THE on regulating ligand‐specific RMT in BBB by inhibiting alkaline phosphatase (ALPL). The study provides a potential strategy candidate or targeted dietary patterns to prevent and treat AD by improving the BBB function. Abstract : The effects of Antarctic krill oil (AKO) combined with nobiletin (NOB) and theanine (THE) on aging‐induced blood−brain barrier (BBB) impairment are investigated, including tight junction, ligand‐specific receptor‐mediated transcytosis (RMT), and non‐specific caveolar transcytosis in brain endothelial cells. The results suggest that AKO exhibits synergistic effects with NOB and THE on regulating ligand‐specific RMT by inhibiting alkaline phosphatase (ALPL).